2001
DOI: 10.1097/00006842-200109000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Premenstrual Symptoms in Women With Schizophrenia: A Prospective Study

Abstract: The findings of this study suggest that premenstrual exacerbation of schizophrenic symptoms in female patients may not be a worsening of the schizophrenic symptoms but a concurrence of affective, behavioral, and somatic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Several studies have recently confirmed earlier findings of disturbed gonadal function and hypo-estrogenism in women with schizophrenia [1,27,35,39,44,[56][57][58][59][60][61]. They described menstrual irregularities and reduced blood levels of estradiol, progesterone and gonadotropins (follicle-stimulating hormone, luteinizing hormone) throughout the menstrual cycle, plus anovulation in the majority of women with schizophrenia and related psychoses.…”
Section: Hypo-estrogenism In Women With Schizophrenia (The Hypothesismentioning
confidence: 53%
See 1 more Smart Citation
“…Several studies have recently confirmed earlier findings of disturbed gonadal function and hypo-estrogenism in women with schizophrenia [1,27,35,39,44,[56][57][58][59][60][61]. They described menstrual irregularities and reduced blood levels of estradiol, progesterone and gonadotropins (follicle-stimulating hormone, luteinizing hormone) throughout the menstrual cycle, plus anovulation in the majority of women with schizophrenia and related psychoses.…”
Section: Hypo-estrogenism In Women With Schizophrenia (The Hypothesismentioning
confidence: 53%
“…For example, a more recent study [35], reported behavioural, affective and somatic symptoms of schizophrenia (not psychotic ones) to be associated with the menstrual cycle phase. Estradiol was not measured.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…44 Schizophrenia may be an example of an underlying disorder that does not have premenstrual exacerbation of psychotic symptoms but may have superimposed affective and anxiety symptoms of PMDD. 45 The prevalence of premenstrually exacerbated axis I disorders is unknown. It is generally recommended that clinicians treat the underlying disorder first, and if premenstrual symptoms persist, subsequent daily ratings can identify PMDD.…”
Section: Epidemiologymentioning
confidence: 99%
“…In the same line of evidence, Halonquist et al [44] observed lower psychopathology scores in schizophrenic women at the mid-luteal phase compared with the early folicular phase of the menstrual cycle. In a more recent study, however, Choi et al [45], examining the course of symptoms during the menstrual cycle in 30 inpatients with schizophrenia, found that affective and somatic symptoms worsened in the premenstrual period, but not psychotic symptoms. Recently, another research team [46] has aimed at studying this question in a sample of 50 women with schizophrenia hospitalized for an acute episode, measuring levels of estrogens, progesterone, follicle-stimulating hormone, luteinizing hormone and prolactine, and comparing with healthy controls and patients with other psychiatric diagnoses.…”
Section: Estrogenic Theorymentioning
confidence: 93%